Commodity risk assessment of Ligustrum delavayanum topiary plants grafted on Ligustrum japonicum from the UK. (11th November 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as 'High risk plants, plant products and other objects'. This Scientific Opinion covers plant health risks posed by evergreen 3‐ to 20‐year‐old topiary plants of Ligustrum delavayanum grafted on L. japonicum in pots imported from the UK, taking into account the available scientific information, including the technical information provided by the UK. All pests associated with the commodity were evaluated against specific criteria for their relevance for this Scientific Opinion. One EU quarantine pest ( Scirtothrips dorsalis ), one EU protected zone quarantine pest [( Bemisia tabaci (European populations)] and two EU non‐regulated pests ( Diaprepes abbreviatus and Epiphyas postvittana ) fulfilled all relevant criteria and were selected for further evaluation. For the selected pests, the risk mitigation measures described in the technical dossier from the UK were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. While the estimated degree of pest freedom varied among pests, E. postvittana was the pest most frequently expected on the commodity. The Expert Knowledge Elicitation indicated, with 95% certainty, that 9, 724 or more living sculptures per 10, 000 would be free from E. postvittana .